B-Cell chronic lymphocytic leukemia fluorescence in situ hybridization panel findings at tertiary care hospital in Saudi Arabia - Wedian Mustafa Rawas; Salem H Khalil; Emad E Ghabashi (Journal of Applied Hematology, 2018)
BACKGROUND/PURPOSE: B-cell-chronic lymphocytic leukemia (B-CLL) is the most common leukemia in the Western world and shows a remarkable heterogeneity in the clinical course. Understanding the genetic basis of B-cell-CLL may help in clarifying the molecular bases of this clinical heterogeneity. Recurrent chromosomal aberrations at 13q14, 12q15, 11q22-q23 and 17p13, and TP53 mutations are the first genetic lesions identified as drivers of the disease. While some of these lesions are associated with poor outcome (17p13 deletion, TP53 mutations and to a lesser extent, 11q22-q23 deletion), others are linked to a favorable course (13q14 deletion as sole aberration). This study evaluates the frequency of each chromosomal abnormality using fluorescence in situ hybridization (FISH) Panel at our institution with comparison to other international studies. MATERIALS AND METHODS: We reviewed 147 peripheral blood and bone marrow samples which represent all B-cell-CLL cases diagnosed at our hospital from 2012 to 2016 by morphology and flow cytometry immunophenotyping followed by specific B-cell-CLL-FISH panel including MDM2/Cen12 for Trisomy 12, 13q14 (D13S319)/13q34 deletion, ATM (11q22.3) deletion, P53(17p13.1) deletion, and CCND1/IGH translocation (11;14). RESULTS: Between 2012 and 2016, a total of 147 B-cell-CLL patients were investigated using B-cell-CLL-FISH panel at our institution King Faisal Specialist Hospital and Research Center-Riyadh, Kingdom of Saudi Arabia, with age ranging between 36 and 89 years and a median age of 62 years. The majority of the patients with the abnormal FISH pattern, 70% (73/105), had a single abnormality with the remaining 30% (32/105) showed more than one genetic abnormality including two cases where all five probes were positive. CONCLUSION: The heterogeneous clinical course of B-CLL is likely explained by underlying molecular prognostic factors including data from FISH probes. Moving forward, analyzing these factors at diagnosis is recommended for better prognostication and outcome of the disease.